Sea level rise impacts and adaptation measures in coastal areas of Bangladesh - Roy, Bishwajit (2023)
This PhD study delves into the multifaceted climate hazards faced by Bangladesh, a low-lying developing country in Southeast Asia, and their profound impact on the lives and livelihoods of coastal communities. While previous research has predominantly focused on specific disasters such as salinity intrusion, flooding, and tropical cyclones, this study takes a comprehensive approach by examining the collective influence of different climate hazards on coastal ecosystems at the first stage. Following that, a particular emphasis is placed on understanding the role of sea level rise (SLR) and its repercussions on local communities. The research methodology employed a combination of tools, including the utilization of the Google Earth Engine API for assessing surface water dynamics, extensive literature reviews, statistical analysis, and modelling to evaluate historical and projected trends of SLR. Additionally, a participatory research action framework was adopted to engage with local communities in two case study areas, Banishanta and Sutarkhali. Through this approach, the study investigated the perceptions of these communities regarding the physiographic impacts of SLR and examined locally-led adaptation strategies aimed at mitigating the effects of SLR-induced impacts. The results of the study demonstrate the significant influence of both climate hazards and human interventions on surface water dynamics in the coastal cities of Bagerhat and Satkhira, aligning with existing research findings. Analysis of SLR trends revealed that Bangladesh has experienced a mean SLR of 4.89 mm/yr in recent decades, almost twice the global average. Furthermore, under different SLR scenarios and emission targets compared to the 1986-2015 period, it is projected that Bangladesh will face even higher SLR rates until the end of the century. Through community engagement, five major SLR-induced impacts were identified: increased salinity, rising water levels, land erosion, waterlogging, and the emergence of char land. Among these, salinity increase, and land erosion were found to inflict substantial economic losses on agricultural activities. The study also scrutinized the existing adaptation measures, incorporating the perspectives and criticisms of the coastal communities. Informed by these insights and expert consultations, two distinct adaptation pathways were proposed as the culmination of the research. The study underscores the importance of incorporating the participation and perceptions of local communities into future adaptation planning and implementation for successful and sustainable outcomes. Policymakers are urged to account for local physiographic factors and socioeconomic needs during the planning stages of adaptation actions. The findings of this study serve as a foundation for further investigations into SLR-induced vulnerability and risk analysis in Bangladesh's coastal areas. Additionally, they provide valuable guidance to coastal landscape planners and policymakers in formulating and promoting feasible adaptation policies tailored to the economic activities of the coastal communities.